ANALISIS PERHITUNGAN HARGA POKOK TEMPE KEDELAI MEMAKAI METODE FULL COSTING - Teuku Alfiansyah; Ahmad Septian, Rijal Anjani, Paduloh (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
Calculating production costs through a full costing procedure is considered to be a step that is very much in line with business studies because this procedure carefully covers all budget aspects that play a role in the production process. The essence of this research is an effort to observe and reflect on the comparison between estimated production costs through full costing calculations and detailed components of the soybean tempeh production budget. Related to this exploration, the findings show that the cost of production which is explained in detail in the full costing procedure shows an increasingly higher figure when compared to the production costs calculated using the basic Soy Tempe procedure.